Aporphine alkaloids from the leaves of Phoebe grandis (Nees) Mer. (Lauraceae) and their cytotoxic and antibacterial activities - Omar, H.; Hashim, N.M.; Zajmi, A.; Nordin, N.; Abdelwahab, S.I.; Azizan, A.H.S.; Hadi, A.H.A.; Ali, Hapipah Mohd (2013)
The oxoaporphine alkaloid lysicamine (1), and three proaporphine alkaloids, litsericinone (2), 8,9,11,12-tetrahydromecambrine (3) and hexahydromecambrine A (4) were isolated from the leaves of Phoebe grandis (Nees) Merr. (Lauraceae). Compounds 2 and 3 were first time isolated as new naturally occurring compounds from plants. The NMR data for the compounds 2–4 have never been reported so far. Compounds 1 and 2 showed significant cytotoxic activity against a MCF7 (human estrogen receptor (ER+) positive breast cancer) cell line with IC50 values of 26 and 60 µg/mL, respectively. Furthermore, in vitro cytotoxic activity against HepG2 (human liver cancer) cell line was evaluated for compounds 1–4 with IC50 values of 27, 14, 81 and 20 µg/mL, respectively. Lysicamine (1) displayed strong antibacterial activity against Bacillus subtilis (B145), Staphylococcus aureus (S1434) and Staphylococus epidermidis (a clinically isolated strain) with inhibition zones of 15.50 ± 0.57, 13.33 ± 0.57 and 12.00 ± 0.00 mm, respectively. However, none of the tested pathogenic bacteria were susceptible towards compounds 2 and 3.